EVALUASI STRATEGI PROMOSI DALAM MENINGKATKAN MINAT CALON MAHASISWA BARU DAN KEBERHASILAN STUDI DI PTS SSS MENGGUNAKAN REGRESI DAN ANOVA - Arijanto, Sugih; Mulqi, Selvi Aulia (Teknik Industri Unikom, 2025)
PTS SSS as one of the Private Universities has implemented various promotional strategies and selection paths to attract new students, both in terms of quantity and quality, but their effectiveness has never been measured. The purpose of this study is to evaluate promotional strategies and test significant differences between various selection paths and school-based accreditation at PTS SSS. The AIDA approach and effectiveness and efficiency testing with various indicators such as ROI, Conversion Rate, Response Rate to evaluate promotional strategies as well as ex post facto methods for study success. The results of the study show that promotional strategies through social media are more effective in reaching a wider audience at a lower cost, while direct selling promotions generate more new students but incur higher costs. Based on Anova, the PMDK new student admission selection path produces new students who have the highest study performance compared to UTBK, USM and finally ODT. Based on regression analysis, it was found that school-based accreditation had a significant effect on study performance.